Tingkat Pengetahuan Gizi Ibu Dan Praktik Pemberian Makanan Pendamping ASI Dengan Status Gizi (BB/U) Baduta - Dwi Ulfa Kurniasih; Alifiyanti Muharammah; Masayu Dian Khairani; Desti Ambar Wati (Journal of Innovative and Creativity, 2025)
Nutritional problems in children under two years of age (under-five) are influenced by various factors, including direct factors related to food intake and infection. The adequacy of food intake is highly dependent on the knowledge of mothers as food providers as well as the practice of feeding complementary foods to baduta. The study purpose was analyze the relationship between the level of maternal knowledge and complementary feeding practices with nutritional status based on the indicator of body weight according to age (BB/U) in under-fives aged 6-23 months in the working area of UPTD Puskesmas Kedondong in 2024. This study is a quantitative study with a cross-sectional design. The instruments used included questionnaires, questionnaires, and anthropometric tables (BB/U). The study sample consisted of 101 mothers of infants, who were selected using the quota sampling technique in three villages of the UPTD Puskesmas Kedondong working area, namely Sinar Harapan Village, Kertasana Village, and Tempel Rejo Village. Bivariate data analysis was conducted using the gamma correlation test. The study showed a significant relationship between the level of maternal nutrition knowledge (p = 0.000), complementary feeding practices based on age (p = 0.000), texture (p = 0.013), quantity (p = 0.000), frequency (p = 0.000), and variety (p = 0.021) with nutritional status (BB/U) in children aged 6-23 months. “There is an average relationship between the level of maternal knowledge and the practice of breastfeeding MP with nutritional status” according to BB/U of 6-23 months old infants at UPTD Puskesmas Kedondong in 2024.